FAKTOR-FAKTOR YANG MEMPENGARUHI KENYAMANAN DAN KUALITAS PEMAKAI LENSA PROGRESIF - Wahyu Budiana (Jurnal Mata Optik, 2021)
The comfort and quality of vision of progressive lenses are determined by several factors such as the measurement and placement of the lens, the position of the head when examined, and the adjustment of the eyeglass frame when the lens parameters are measured. This research illustrates how the comfort and quality of vision can be affected by these factors. This research was conducted on those who have examined and installed progressive lenses based on their experience and abilities. The results showed that the visual quality of progressive lens wearers was influenced by the measurement of monocular PD, vertical pupils with reference to the lower rim of the rim and the center of the pupil,. head position factor when looking far must be in a straight or primary position, factors that affect the quality of vision where far vision must be clear through progressive lenses , quality near vision must be clear and distance vision medium clear.